Travels and itineraries of the Roman emperors: an interview with Ana Teresa Marques Gonçalves - Gonçalves, Ana Teresa Marques (Romanitas - Revista de Estudos Grecolatinos, 2022)
Interview with Ana Teresa Marques Gonçalves.
Keywords: Interview; Ana Teresa Marques Gonçalves; Travels; Itineraries; Roman emperors